What point does it lie on?
1 Answer
It generally helps to identify the equation for
The two graphs superimposed onto each other look like this:
graph{((x-1)^2 - 3 - y)(sqrt(x+3)+1 - y)(-sqrt(x+3)+1 - y) = 0 [-17.44, 23.11, -10.89, 9.39]}
METHOD 1
An inverse is defined so that some coordinate
So, to work backwards, select each answer and invert its coordinates from
#(3,1) -> (1,3)# , which is not on#f(x)# .#(2,-2) -> (-2,2)# , which is not on#f(x)# .#(1,-3) -> (-3,1)# , which is not on#f(x)# .#color(blue)((-3,1) -> (1,-3))# , which is on#f(x)# .
To be clear, this means that
METHOD 2
Or, we could construct an equation for
This means
#f(x) = a(x-1)^2 - 3# remembering that
#a(x + h) + k# shifts left by#h# units and up by#k# units, sign included.
So now, given one point
#1 = a(3 - 1)^2 - 3#
#4 = 4a#
#=> a = 1#
and the equation should be
graph{(x-1)^2 - 3 [-10, 10, -5, 10]}
The more mathematical approach then is to take
#y = (x-1)^2 - 3#
and swap
#x = (y-1)^2 - 3#
#x + 3 = (y - 1)^2#
#=> color(blue)(y = f^(-1)(x) = pm sqrt(x + 3) + 1)#
which looks like this:
graph{(sqrt(x+3) + 1 - y)(-sqrt(x+3) + 1 - y) = 0 [-4.96, 15.04, -3.88, 6.12]}
From here you can see that since
#(1) stackrel(?" ")(=) cancel(pmsqrt((-3) + 3))^(0) + 1#
#=> 1 = 1#
which shows that